High resolution in three dimensions with SWIFT and PALM3K - Clarke, F; Thatte, N; Tecza, M; O'Brien, K; Houghton, R; Tice, D; Fletcher, L; Irwin, P; Verma, A; Dekany, R; Buruss, R; Roberts, J (INAF - Osservatorio Astrofisico di Arcetri Largo Enrico Fermi, 2013)
SWIFT is a visible light (650-1000nm) integral field spectorgaph fed by the Palomar extreme adaptive optics system PALM3K. With a subaperture spacing of 8cm, PALM3K is capable of delivering diffraction limited performance even in the visible. With SWIFT providing spatially resolved spectroscopy at R=4000, this provides a truly unique facility for high resolution science in three dimensions. We present here some results from the first year of PALM3K+SWIFT science. We also report on our experience of operating a small field of view instrument (1"x0.5") with a high performance AO system, and hope the lessons learned will provide valuable input to designing successful and productive AO plus Instrument combinations for ELTs.